Sensory Characteristics Of Madura Black Spice Based On Duck - Alfin Maghfiroh; Hari Minantyo (Universitas Negeri Padang, 2026)
This study aims to analyze the manufacturing process, organoleptic quality, and marketing strategy of Madura black spice made from duck with variations in duck liver composition. The method used was an experiment with organoleptic tests on 90 panelists using a Likert scale to assess color, aroma, taste, and texture, and statistical analysis using SPSS. The results showed that the best formulation was treatment B2 (75%), which obtained the highest scores on all parameters with a good level of assessment consistency. ANOVA tests showed significant differences between treatments in all parameters. An effective marketing strategy uses the 5P marketing mix concept with production cost-based pricing, accessible distribution, digital promotion, and attractive and informative packaging. Initial sales showed an increasing trend with stable turnover, and interview results indicated that the product has good acceptance in the market although variant development is needed to reach wider consumer preferences. This study concluded that formulation B2 is worthy of being developed as a superior product with good commercial potential.